(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Genetic studies are one of the gold standards to back up data on prevalence, survey, and genetic association with common diseases and disorders. The extraction of optimal quantities of DNA samples forms an integral part of genomic studies. This literature search gives an insight into the various methods available for DNA isolation. Further, a comparative evaluation was done to validate which would be the optimal method of sample collection, based on factors such as degree of invasiveness, the quantity of sample required, good storage capability, and cost-effectiveness. Genetic studies that are conducted on a huge population involve a large number of samples from the participants are often needed when conducting genetic studies and this validates a need for many factors considered when selecting the optimal source of sample collection. . The different methods of sample collection compared were a) Venous blood, b) Saliva, c) Buccal Swabs, d)Buccal cell swabs on FTA cards, e) Hair and Urine Samples. A comparison of the various methods would be discussed and the advantages and disadvantages of the various method would be systematically analyzed to give the clinician/researcher a better insight to choose the right method of sample collection based on the facilities available for DNA isolation.